Evaluation of the Community Association Empowerment Program in Accelerating Development in Sukabumi City - Restiana, Nada; Meigawati, Dine; Mulyadi, Andi (International Journal of Education, Information Technology, and Others, 2024)
This study evaluates the Rukun Warga Empowerment Program (P2RW) in Sukabumi City to assess the effectiveness of implementation and its impact on the community. Problem phenomena identified included challenges in program implementation, such as a long bureaucracy and lack of socialization of the new SIPD system, as well as variability in implementation in different areas. The purpose of the study is to evaluate the program implementation process, outputs, and outcomes of P2RW to identify the strengths, weaknesses, and impacts of the program on infrastructure development and community empowerment. The research method used is the CIPP (Context, Input, Process, Product) model evaluation approach, with data collection through interviews, observations, and document analysis. The results showed that the P2RW program successfully improved physical infrastructure and empowered local communities, by involving them in project planning and implementation. However, there are challenges in socializing the SIPD system and bureaucratic constraints that affect implementation efficiency. The program contributes to improving the quality of life of residents and accelerating development at the RW and RT levels, although there is a need for improvement in technical support and socialization to optimize program implementation. This study recommends further research to explore these aspects in more depth.